Nutrição e crescimento inicial de cana-de-açúcar fertilizada com concentrado de vinhaça biodigerida em condições de vaso - Ortega, Kamilla [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Com o objetivo de estudar o comportamento do concentrado de vinhaça biodigerida (CVB) em relação à vinhaça in natura (VN), no crescimento e na nutrição de plantas de cana-de-açúcar, foi desenvolvido um experimento em vasos contendo a combinação de dois solos (latossolo e argissolo), com dois níveis de fertilidade (sem e com a correção da fertilidade) e com quatro tratamentos qualitativos em relação ao K (sem adição de K; com VN na dose de 100 m³ ha-1, com CVB ou KCl em dose de K igual à da VN). Os resultados revelaram que houve comportamento similar entre as vinhaças, tanto na ausência como na presença da correção da fertilidade do solo, sendo que para o concentrado de vinhaça biodigerida os valores tenderam a serem inferiores. O latossolo na ausência da correção da fertilidade induziu maiores resultados para crescimento e nutrição das plantas, em relação ao argissolo, por ter fertilidade original melhor. Porém na presença da correção da fertilidade o latossolo induziu menores resultados. A correção da fertilidade do solo é fundamental para se obter melhores respostas para o crescimento e nutrição da planta de cana-de-açucar, assim tanto o latossolo quanto o argissolo, bem manejados, podem proporcionar bons resultados

In order to study the effect of concentrated of biodigested vinasse (CVB) compared to in natura vinasse (VN) on the growth and nutrition of sugar cane plants, an experiment was conducted in pots containing a combination of two soils (Oxisol and Ultisol) with two fertility levels (with and without fertility correction) and with four qualitative treatments related to K (control = without addition of K; with VN in a dose of 100 m³ ha-1; with CVB or KCl at a dose of K equal to the VN). The results showed that with soil fertility correction, the CVB had similar behavior regarding to plant height, stem diameter, internodes number, leaf area, K and Mg content, and accumulation of P. The VN promoted higher values for P content, and accumulation of Cu and K, N, Ca, S and Cu. In the absence of soil fertility correction, CVB was similar to overall plant growth and accumulation of K, N, Ca, S and Cu; the highest values for VN on K content and higher values for CVB regardong to Mg, P and Cucontent, and accumulation of P. In the Oxisol, both vinasses induced similar values for content of K, S, Cu and Mn, and accumulation of S, N, Ca, Mg, Mn and Zn. In the Ultisol vinasses had similar values for content of Mg, Cu and Mn, and Ca, Mg, Mn and Zn accumulation. The highest values of K and S levels, and S and N accumulation were found when plants were fertilized with VN. Both vinasses showed better results of K, Mg and Cu content in the Oxisol. The VN had similar behavior on both soils for S content, and induced higher values for Zn accumulation in Ultisol. The CVB induced higher values for S content and accumulation of Mg in both tested soils
Keywords: Adubação; Cana-de-açúcar - Adubação potássica; Biodigestão anaeróbia; Vinhaça biodigerida; Sugarcane - Potassium fertilization; Vinasse; Anaerobic digestion